Strategi Pemasaran Akibat Perubahan Consumer Behaviour - Arisa Ananda (Universitas Pendidikan Nasional, 2018)
ABSTRACTThe current era of information system development has changed the business landscape from conventional marketing model to digital marketing. With the development and breadth of internet usage, travelers are getting easier to find information and plan their holidays. The purpose of this study is to find out how the implementation of marketing strategy to change consumer behavior in increasing the occupancy rate of rooms at The L Hotel & Resort, in this study researchers used a qualitative approach where in this study more emphasis on meaning and process than the result of an activity. In qualitative research the usual methods used are interviews, observation and utilization of documents. The results of this study found that The L Hotel & Resort has not optimized the digital marketing in marketing strategy, both in terms of use of digital marketing tools itself to human resources who do marketing. This can be seen from the number of cooperation with OTAs and less utilized web hotel, from the analysis of interviews to the informants obtained that the website and social media The L Hotel & Resort is still less qualified, there are many weaknesses and not up to date. It certainly has an impact on the marketing of hotel rooms online that tend not to meet the target.